Evaluation of the micro-tensile bond strength of three self adhesive bulk-fill resin composites compared to a reinforced glass ionomer restoration and their failure modes - Ahmed Tharwat Al Ammary, Walaa Mohamed Ahmed Alsamoully, Ibrahim El Dossoky Basha, Hamed Ibrahim Mohamed Ibrahim, Mahmoud El-Said Ahmed Abd El-Aziz, Alaa.N. Syam, Mahmoud Abdellah Ahmed Refaei, Hosam Muhammad Elsayed (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Aim: The current research aimed to evaluation the μ-TBS of three self-adhesive bulk-fill resin composites compared to a reinforced glass ionomer restoration, and its failure modes by stereomicroscopy. Method: 40 human permanent mandibular molars were selected to be utilized in the present research. Each molar has sectioned to 4 mm occlusal to cementoenamel junction. The roof of pulp chamber of each tooth was removed by taper stone bure with high-speed hand piece for making place for putting the tested filling materials.